Effectiveness of virtual and augmented reality-enhanced exercise on physical activity, psychological outcomes, and physical performance: A systematic review and meta-analysis of randomized controlled trials. (October 2019) - Ng, Yu-Leung; Ma, Flora; Ho, Frederick K.; Ip, Patrick; Fu, King-wa
Abstract: Virtual reality (VR) and augmented reality (AR)-enhanced exercise training is a novel approach to promoting health. Previous systematic reviews have focused on the effectiveness of VR interventions in clinical settings. The present study was the first systematic review to investigate the effectiveness of exercise-based VR and AR training as preventive measures in improving physical activity, psychological outcomes, and physical performance of a healthy population when compared with traditional programs and no-exercise controls. This study included 22 research articles published between 1997 and 2017, involving 1, 184 participants aged 18 to 79. The results showed a large effect on physical activity (Hedges' g  = 0.83, SE  = 0.18), a small to moderate effect on physical performance (Hedges' g  = 0.31, SE  = 0.09), and no significant effect on psychological outcomes. VR training programs were particularly shown to be effective for enhancing frequency of physical activity and strength of physical performance. Only two studies examined the effectiveness of AR training programs on physical performance, and the findings concerning those effects were not separately reported. A list of plausible moderators was tested but that variable was not significantly associated with the effects of VR on the three outcomes. Limitations and future directions are discussed. Highlights: This study compared VR- and AR-exercise and traditional and no-exercise programs. VR training programs were effective for enhancing frequency of physical activity. VR and AR programs were effective for improving strength of physical performance. Further studies of AR-enhanced exercise using randomized controlled trials are warranted.